2011
DOI: 10.2527/jas.2010-3306
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of urinary zearalenone concentrations for monitoring natural feed contamination in cattle herds: On-farm trials1

Abstract: The aims of the present study were to investigate the efficacy of measuring bovine urinary zearalenone (ZEN) concentrations by using a commercially available ELISA method in cattle kept under different feeding conditions to monitor the natural contamination of feeds at the farm level, and to investigate the effects of supplementation of a mycotoxin adsorbent (MA) product in the feed based on urinary ZEN concentration. First, Japanese Black cattle herds kept for breeding (4 herds) and fattening (4 herds) purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 27 publications
1
50
0
2
Order By: Relevance
“…In our previous study (Takagi et al 2011), it was clearly indicated that MA-A supplemented as TMR (theoretically equally mixed with the feed diets) was effective in preventing the adsorption of ZEN from the intestines of dairy cattle. Thus, as a preliminary study, we examined whether the method of supplementing MA within the feed diets may have an effect on the urinary concentrations of ZEN and its metabolites.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study (Takagi et al 2011), it was clearly indicated that MA-A supplemented as TMR (theoretically equally mixed with the feed diets) was effective in preventing the adsorption of ZEN from the intestines of dairy cattle. Thus, as a preliminary study, we examined whether the method of supplementing MA within the feed diets may have an effect on the urinary concentrations of ZEN and its metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, it was assumed that the method used to supply the MA into the feeds might have a significant effect on the extent of absorption of mycotoxin from gastrointestinal tracts. However, MA supplementation revealed that it was not possible to adsorb ZEN and its metabolites completely from naturally contaminated feeds, even if supplied with a maximum dose of MA to the TMR for a period exceeding 2 weeks as recommended by the manufacturer (Takagi et al, 2011). Although we cannot simply compare the total ZEN concentrations between our previous and present studies because of the differences of breed of cattle and body weights, the minimal concentration of total ZEN in previous report was approximately 400 pg/mg Crea as determined by ELISA and 100 pg/mg Crea as determined by LC/MS/MS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations